The lost history of the Ninth Amendment - Lash, Kurt T. (New York ; Oxford : Oxford University Press, 2009)
The most important aspect of this book is its presentation of newly uncovered historical evidence which calls into question the currently presumed meaning and application of the Ninth Amendment.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- History; Civil rights -- United States; Constitutional law -- United States